Tank cascade systems of Sri Lanka: Resilient rural landscapes for people, food and nature - Mendonce, Sharon; Ratnayake, Sujith; Borelli, Teresa; Hunter, Danny; Silva, K.A.I.D.; Cutrin, Agnese (2024)
Designated a Globally Important Agricultural Heritage System in 2017, the Tank Cascade System (TCS) is an ancient, man-made water management system unique to Sri Lanka’s dry zone. This book provides a comprehensive understanding of the TCS and the broader landscape (i.e., cascade landscape) it occupies. Further, the book highlights research and fieldwork conducted under the GEF-funded Healthy Landscapes Project (HLP). Implemented between 2018 and 2024, the HLP brought together multiple local, national and global-level partners to rehabilitate the TCS and ensure its sustainable management. The project used a landscape approach, focusing on mainstreaming biodiversity and strengthening cascade ecology. The HLP serves as a model for future projects and programmes aimed at safeguarding the TCS and offers valuable insights into the links between biodiversity, food and nutrition security, climate resilience and rural livelihoods in cascade landscapes.